India: Sustainable Access in Rural India (SARI) project - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Sustainable Access in Rural India (SARI) project seeks to show that viable markets exist for information and communication services in rural poor areas by inventing and deploying innovative technologies, assessments, and business models. The ultimate